Antara Label Halal Dengan Keputusan PembelianDalam Perspektif Hukum Ekonomi Syariah - Andi Fariana; Ahmad Lutfi Rijalul Fikri (TAFAQQUH, 2022)
This study aims to examine the influence of halal labeling on consumer purchasing decisions in Indonesia, considering the rapid innovation in food products and the importance of information related to product halal status. Employing a qualitative descriptive method, this research explores relevant journals, compares findings, and analyzes pertinent regulations and fatwas. The results indicate that halal labels on products significantly influence purchasing decisions for both food and non-food products, such as cosmetics, with consumers feeling more secure and confident about the products' halal status. This study highlights the crucial role of government regulations and certification bodies like MUI and BPJPH in ensuring product halal compliance, providing guidance for producers to attract consumer interest through clear halal labelling